ANALISIS PENGENDALIAN KUALITAS PRODUK SARUNG TANGAN DENGAN METODE STATISTICAL QUALITY CONTROL PADA PT ADI SATRIA ABADI - Jonat Jannata Tampana Putra; Suseno Suseno (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
PT Adi Satria Abadi, a leather glove manufacturer, continues to experience product defects during its production activities. This study aims to identify the most frequent defects, evaluate the effectiveness of quality control, analyze the factors contributing to product defects, and recommend corrective actions. Statistical Quality Control (SQC) was employed using check sheets, Pareto diagrams, histograms, p-charts, scatter diagrams, fishbone diagrams, and 5W+1H analysis. The study found that 20,883 defective products were recorded out of 220,839 units produced. Misplaced stitching was the most common defect (41.22%), followed by skewed defects (31.19%), non-oval defects (17.15%), and wrinkled defects (10.44%). The p-chart indicated that the production process was not entirely under statistical control due to one point exceeding the upper control limit (UCL), while the scatter diagram showed a positive relationship between production volume and defect occurrence. Fishbone analysis identified human, method, machine, material, and environmental factors as the main causes of defects, with human and method factors contributing the most. Improvement proposals generated through the 5W+1H method include operator training, stricter SOP implementation, preventive maintenance, tighter material inspection, and improvements to the workplace environment. These recommendations are expected to reduce product defects and improve product quality. Keywords: Statistical Quality Control (SQC), quality control, leather gloves, product defects, fishbone diagram